EVALUATING THE STRESS LEVEL OF HOSPITAL PHARMACIST AT PEAK HOURS WORK OF PHARMACY: PREVALENCE, DETERMINANTS, AND RECOMMENDED SOLUTIONS (Journal of Medical & Health Sciences Review, 2025)
BackgroundPharmacy stress is an increasing issue that may negatively impact job performance and patient safety due to workplace stress among the pharmacy staff. This research was intended to determine the degree of stress, its contributing factors, coping mechanisms and possible remedies among pharmacy professionals.ObjectivesTo measure the level of stress in the workplace, determine key stressors, measure the effects of these stressors, research the potential coping strategies, and identify the stress reduction strategies that staff members would recommend.MethodsThe survey was done on 100 pharmacy personnel in a cross-sectional study. The information was gathered on demography, workload pattern, frequency of stress, the factors contributing to it, its effects on patient safety, coping strategies, and the solution to it. The findings were summarised using descriptive statistics.ResultThe sample size was 67 percent female and 40 percent with 1-3 years of working experience. 66% of respondents indicated the morning shift (8 12 PM) to be the busiest. Most of them, over 51% (n=42), filled more than 150 prescriptions per day, and 60% of them indicated that they were understaffed. There was a high prevalence of stress, with 43% reporting always having stress and 20% reporting having it frequently. High patient load (34%), absence of staff support (25%), multitasking and interruptions (14%), and absence of automation (13%) were considered major stress factors. 62% of participants interfered with patient safety on a regular or even frequent basis. The most frequent coping mechanisms were team support (43%) and short breaks (28%). The proposed resolutions were the employment of additional personnel (43%), digital automation (23%), and an improved shift schedule (13%).Conclusion Workload, shortages of staff and inefficiencies in the workflow (which may compromise patient safety) are major forms of stress that pharmacy staff experience in the workplace. The interventions at the system level (additional staffing, further workflow automation, organisational support) are necessary to improve staff well-being and provide safer patient care.